THE EFFECTIVENESS OF THE READ, ANSWER, DISCUSS, EXPLAIN, AND CREATE (RADEC) LEARNING MODEL ASSISTED BY FLASHCARD MEDIA IN IMPROVING STUDENTS' UNDERSTANDING OF SCIENCE CONCEPTS IN ELEMENTARY SCHOOL - Asep Samsudin; Anugrah Ramadhan Firdaus (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to see the effectiveness of the application of the RADEC learning model on student understanding of alternative energy materials in elementary schools. This research was conducted in one of the Madrasah Ibtidaiyah in Bandung Regency with a sample of class IV as many as 38 students. This research used pre-experiment method with One Group Pretest-Posttest design. The instrument used is a description question about energy material as many as 14 questions that cover indicators of concept understanding. The results showed that the average student pretest score was 7.3 and the average student posttest score was 8.65 this resulted in a gain value of 0.5. Based on the above results, the RADEC learning model assisted by flashcards can improve students' understanding of the concept of energy.